Finite Element Analysis of Interlocking Loadbearing Hollow Block - Sadoun, Idib S. (2000)
The interlocking hollow block system (IHB) is used recently for the construction of loadbearing and non loadbearing walls. The IHB system draws the attention of engineers and scientists all over the world due to its simplicity and lower construction cost, in addition to its good structural performance. The mechanical interlocking between different block units are designed to replace the mortar layers. This study covers the theoretical investigation of different hollow block systems in terms of their mechanical, physical and structural properties. The research focus mainly on the structural analysis of "Putra block" which is an interlocking hollow block system developed recently by the Housing Research Centre at UPM. The analysis of the putra interlocking hollow block has been carried out using the finite element method. The Finite Element analysis covers the structural behaviour of an individual block, interlocking prism and panel walls using different types of interlocking blocks i.e. stretcher, half and corner block, under vertical and horizontal loads. The structural behaviour of individual blocks, prisms and wall panels are studied in terms of stress distribution, deformation and the location of the maximum stresses as well as failure load. In addition, the effect of eccentricity of the vertical axial load on the ultimate load capacity of the wall panel has been investigated. The maximum compressive stresses developed in the individual blocks (stretcher, half and comer block) are 3.92 MPa, 3.16 MPa and 2.95 MPa respectively, while the maximum tensile stresses are 1.47 MPa, 1.43 MPa and 0.92 MPa respectively. Interlocking block prism has been modeled using interface elements between blocks. The maximum compressive and tensile stresses have been found to be equal to 4.65 MPa and 2.38 MPa respectively. A panel wall with dimensions of 1200 mm W x 1200 mm H x 150 mm T has been elastically analysed under unifomtly distributed load. The result obtained indicates that the stress distribution is similar to the stress distribution observed in the prism. Interlocking block panel has been nonlinearly analyzed under concentric and different eccentricities loading (0.05t, O.lt, 0.2t, and O.3t). The failure loads obtained were 25.63, 24.0, 22.4, 19.95 and 17.96 N/mm2 respectively. The efficiency of the panel wall with the increase of the eccentricity of the load have been compared with the experimental observations. Panel walls with heights of 2.0 m, 2.4 m and 3.0 m have been nonlinearly analysed under lateral load and the maximum lateral displacements observed in different walls are 6.96 mm, 8.28 rom and 11.89 rom respectively. The failure load decrease with increasing the height of the panel. The joint opening in the tensile side of the wall has been observed. The opening suddenly increases to a large value when the applied load approaches the failure stress, indicating a brittle failure mechanism. The overall conclusions drawn from this investigation indicates that the theoretical analysis performed in this study indicates possible cracking in the webs when the putra block is used to construct loadbearing walls in 5-storey buildings and considered critical. This is due to neglecting the geometric nonlinearity and initial imperfection, which is quite possible in the construction field. the construction of loadbearing walls in 1-2 storey buildings. While, more comprehensive experimental and theoretical study is required to ensure the applicability of putra block in 5- storey building.